The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1051/0004-6361/201220336
|View full text |Cite
|
Sign up to set email alerts
|

Full spectral fitting of Milky Way and M 31 globular clusters: ages and metallicities

Abstract: Context. The formation and evolution of disk galaxies are long standing questions in astronomy. Understanding the properties of globular cluster systems can lead to important insights on the evolution of its host galaxy. Aims. We aim to obtain the stellar population parameters -age and metallicity -of a sample of M 31 and Galactic globular clusters. Studying their globular cluster systems is an important step towards understanding their formation and evolution in a complete way. Methods. Our analysis employs a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 81 publications
4
39
2
1
Order By: Relevance
“…The other two clusters, B347-G154 and B083-G146, should be old clusters according to their red colours. In the third panel of the figure we compare our results with those from Chen et al (2016) and Cezario et al (2013), who use the full spectral fitting method. The ages of the young clusters from Chen et al (2016) are also estimated from the SED fittings.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…The other two clusters, B347-G154 and B083-G146, should be old clusters according to their red colours. In the third panel of the figure we compare our results with those from Chen et al (2016) and Cezario et al (2013), who use the full spectral fitting method. The ages of the young clusters from Chen et al (2016) are also estimated from the SED fittings.…”
Section: Resultsmentioning
confidence: 87%
“…Ma et al (2012) determined the age and mass of B514 by comparing its spectral energy distribution (SED) with theoretical stellar population synthesis models. Cezario et al (2013) obtained ages and metallicities of 38 M31 and 41 Galactic GCs by comparing their observed integrated spectra with the SSP model spectra on a pixelby-pixel basis. Fan et al (2016) derived ages and metallicities of 22 confirmed M31 GCs and concluded that using a combination of spectroscopic and photometric data resulted more reliable parameters than those from either spectroscopic data only or photometric data only.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of GCs have shown a variety of AMRs in the past, e.g., the Milky Way (Salaris & Weiss 2002;Mendel et al 2007;Leaman et al 2013;VandenBerg et al 2013;Roediger et al 2014), M31 (Jiang et al 2003;Fan et al 2006;Cezario et al 2013), the Large Magellanic Cloud (Carrera et al 2011), and NGC147, NGC185, and NGC205 (Sharina et al 2006). The AMRs found by these studies all share an anti-correlation between age and metallicity, which is expected, as the metallicity of GCs reflects the metallicity of the environment in which they have formed.…”
Section: Amr and The M/l Ratios Of Gcsmentioning
confidence: 99%
“…We take the age and metallicity data of a sample of 38 GCs in M31 from Cezario et al (2013) that has been obtained by using a spectral fitting technique to the observed integrated . The SSP curves in this plot do not include the effect of dynamical evolution.…”
Section: Amr and The M/l Ratios Of Gcsmentioning
confidence: 99%
See 1 more Smart Citation